Critical factors influencing the success of massive open online courses in Malaysian public universities / Nour Awni Albelbisi - Nour Awni , Albelbisi (2019)
The purposes of this study are to investigate the critical factors influencing successful implementation of MOOCs in Malaysia higher education and to propose a model to assess MOOCs success which includes seven factors: system quality, information quality, service quality, student attitude, course quality, self-regulated learning, and satisfaction. The framework of this study was based on DeLone and McLean model that enlisted three factors i.e. learner attitude, course quality and self-regulated learning to reflect the quality of teaching and learning process. A correlation design method was conducted at five public universities who received highest MOOCs enrollment in the Malaysia MOOCs. A 56-item 5-point Likert-scale instrument was then administered to 622 undergraduate students. Data were analyzed using the Partial Least Squares-Structured Equation Modeling (PLS-SEM) approach. Findings revealed that there were significant relationships between three factors (system quality, attitude, and course quality) and students’ satisfaction, and a positive correlation between the factors (i.e. service quality, attitude and course quality) and students’ self-regulated learning (SRL). Findings also indicated that satisfaction have significant mediating effect on the relationship between system quality and SRL, and between attitude and SRL. Additionally, the results confirmed that the proposed model is valid and reliable to measure the success of MOOCs systems. The study contributed to the body of knowledge by providing a valid and reliable model to measure the success of MOOCs systems which will be useful for MOOCs researchers, practitioners, and educational institutions in developing successful MOOCs systems.